Is migration good for trade across MENA region? - Rana N. Al Jallal, Nayef N. Al Shammari, (Opción, 2019)
This study investigates empirically the impact of migrants on trade for Middle East and North Africa (MENA) region. The estimated model is tested using the Poisson Pseudo Maximum Likelihood estimator. Using such approach may successfully deal with issues of zero trade observations by forgoing the traditional ordinary Least Squares (OLS) estimator and the log-log model. Importantly, the main findings show that higher migrant levels lead to higher trade relations between MENA countries and migrant countries. As a conclusion, higher migrant levels in host MENA countries attract more trade with migrant countries.